1997
DOI: 10.1136/gut.40.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of life of patients with intestinal failure on home parenteral nutrition.

Abstract: Background-A study was performed to measure the quality of life of patients receiving home parenteral nutrition (HPN)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 12 publications
1
73
0
3
Order By: Relevance
“…In 44-55 % of patients, normal MADRS scores [0-6] were measured at 3, 6 or 12 months after stroke/TIA. Forty two to 45 % rated MADRS scores in the range 7-19 (mild depressive disorder) and 3.5-10 % of patients rated in the range 20-34 (moderate depressive disorder), none in the range > 34 (severe depressive disorder) [29]. Between 6 and 12 months follow-ups, the percentage of patients with normal MADRS scores showed a trend to decline from 55 % to 44 % (p > 0.05); the percentage of ratings in the "moderate depression" range increased from 3.5 % to 10 % (p < 0.05).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In 44-55 % of patients, normal MADRS scores [0-6] were measured at 3, 6 or 12 months after stroke/TIA. Forty two to 45 % rated MADRS scores in the range 7-19 (mild depressive disorder) and 3.5-10 % of patients rated in the range 20-34 (moderate depressive disorder), none in the range > 34 (severe depressive disorder) [29]. Between 6 and 12 months follow-ups, the percentage of patients with normal MADRS scores showed a trend to decline from 55 % to 44 % (p > 0.05); the percentage of ratings in the "moderate depression" range increased from 3.5 % to 10 % (p < 0.05).…”
Section: Resultsmentioning
confidence: 98%
“…They showed that both measures were highly interrelated and identified predictors of QOL such as disability, female sex and motor impairment. In the present investigation, we also chose the SF-36 questionnaire [21,35] to assess QOL for three reasons: (i) the SF-36 has been validated in patient cohorts with a full range of illness [4] as well as in stroke patients [2,9] (ii) it is acceptable to patients, quick and easy to use [2,4] and (iii) it enables comparisons with various other diseases that have been studied by using the SF-36 [7,20,27,29]. At three timepoints -3, 6 and 12 months poststroke -patients were followed up to determine the timecourse of neurological recovery and the frequency and degree of handicap compared with overall and domain-specific QOL.…”
Section: Introductionmentioning
confidence: 99%
“…Adult patients with intestinal failure on TPN report a worse QOL compared with patients with short bowel syndrome not on TPN and worse than the general population, but a similar QOL to patients with chronic renal failure on dialysis (24)(25)(26)(27). Based on these findings we selected children with end-stage renal disease as a reasonable comparison group.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, recovery to full oral nutrition at 1 year has been foreseen in 70% of Crohn's disease patients but only in 26% of oncologic patients [6][7][8][9][10][11][12].…”
Section: Mmentioning
confidence: 98%
“…Many studies have shown that HPN costs 30%-60% less than hospital PN and may improve patients' quality of life [6][7][8].…”
Section: Introductionmentioning
confidence: 99%